Occupational safety and accident prevention : behavioral strategies and methods - Hoyos, Carl, Graf, 1923- (Advances in human factors/ergonomics, 1988)
Since the early 1970s there has been a considerable growth in the literature published on the topic of human reliability. However, the main emphasis has been on technical aspects of human reliability, rather than on an integrated safety approach combining safety engineering, organization and human factors. Up till now, information on the subject of occupational safety which covers human reliability as one aspect has been widely scattered in technical reviews or briefly mentioned in textbooks.